A kinematic analysis of the backward 2.5 somersaults with 1.5 twists dive (5253b) from the 3m springboard - Walker, C. A.; Sinclair, P. J.; Cobley, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of this case study was to determine the practical application of 3D inertial measurement units and compare angular velocity profiles, key position angles and event timings for the backward 2½ somersaults with 1½ twists (5253B). One male diver performed 11 trials of the 5253B while 3D inertial measurement units (IMU) and high speed video were used to measure kinematic variables. Peak angular velocity about the somersault and twist axes were 900±11deg/s and -1435±28.deg/s, with highly consistent patterns displayed for total flight time (<1%) and peak angular velocity (=2%). A comparison between the 5253B and the backward 2½ somersaults dive (205B) indicated significant kinematic differences at take-off, flight and entry. IMU provide a quick and practical analysis tool for coaches wanting to monitor their athlete`s daily performance.